Joni - Eareckson, Joni (Minneapolis, Minnesota World Wide Publications, 1976)
Autobiography of Joni Eareckson, who at 17 was left a quadriplegic as a result of a diving accident, and who today as an accomplished artist drawing with a pen held in her teeth, describes her struggles and her abiding faith in Christ.
Keywords: Tada, Joni Eareckson. Quadriplegia -- Biography. People with disabilities -- Biography